Meeting global challenges with regenerative agriculture producing food and energy - Schulte, Lisa A.; Dale, Bruce E.; Bozzetto, Stefano; Liebman, Matt; Souza, Glaucia M.; Haddad, Nick; Richard, Tom L.; Basso, Bruno; Brown, Robert C.; Hilbert, Jorge Antonio; Arbuckle, J. Gordon (Springer Nature, 2022)
The world currently faces a suite of urgent challenges: environmental degradation, diminished iodiversity, climate change and persistent poverty and associated injustices. All of these challenges can be addressed to a large extent through agriculture. A dichotomy expressed as ‘food versus fuel’ has misled thinking and hindered needed action towards building agricultural systems in ways that are regenerative, biodiverse, climate resilient, equitable and economically sustainable. Here we offer examples of agricultural systems that meet the urgent needs while also producing food and energy. We call for refocused conversation and united action towards rapidly deploying such systems across biophysical and socioeconomic settings.